THE EFFECT OF GIVING BETEL LEAF EXTRACT THROUGH DRINKING WATER ON BROILER EDIBLE OFFALS - K. A. U, Yanto; Nuriyasa, I M.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2021)
This research aims to determine the giving of betel leaf extract through drinking water to broiler edible offals. This research was conducted in Br. Pande, Dajan Peken Village, Tabanan, for 6 weeks. Chickens used are DOCs raised for 2 weeks. The design used was a completely randomized design (CRD) with 3 treatments and 10 replications. Each replication contained 2 broilers so that the number of chickens used was 60. The treatments were (R0) drinking water without using betel leaf extract ( Piper betle L.), (R1) drinking water with 2% betel leaf extract ( Piper betle L.)  and (R2) drinking water with 4% betel leaf extract ( Piper betle L.). The variables observed were the percentage of head, feet, heart, liver, small intestine, and gizzard. The results showed that the percentage of head, feet, heart, liver, small intestine, and gizzard was not significantly different (P>0.05) between the three treatments. Based on these result can be concluded that up to 4% of betel leaf extract through drinking water has no effect on the percentage of broiler edible offals.   Keywords:  broiler, betel leaf, and edible offals